Menjaga Keberlanjutan Produk Lokal dan Keuangan Keluarga: Peran Perempuan Sebagai Penganyam Bambu di Desa Sidetapa Buleleng Bali Utara - Widiastini, Ni Made Ary; Rahmawati, Putu Indah; Arsa, I Ketut Sida (Jurnal Kajian Bali (Journal of Bali Studies), 2023)
This study aims to describe the role of women bamboo weavers in maintaining the sustainability of family finance and local products of Sidetapa, an old village of Buleleng District, North Bali. Data collected through observation and interviews and analyzed by employing a critical qualitative method using a cultural studies approach. The study revealed that the majority of bamboo craftsmen in Sidetapa Village were women who played their traditional and transitional roles well. Through their work as bamboo weavers, women have been enabling themselves to generate income to help the needs of their family. In maintaining the existence of bamboo-based local products of Sidetapa Village, the women weavers always try to be adaptive to market demand. They also actively engage in training programs provided by external parties with the aim of knowing market developments and improving product quality. The article contributes to our understanding of the double roles of women in handling domestic work and getting income to support domestic needs.